Antibodies to the chlamydial 60 kilodalton heat shock protein in women with tubal factor infertility. - Ault, K A (1998)
INTRODUCTION: Fallopian tube damage and subsequent infertility are common sequelae of upper genital tract infection with Chlamydia trachomatis. This fallopian tube damage is thought to be immune mediated. The 60 kilodalton chlamydial heat shock protein (hsp) may be the key antigen associated with this pathogenic response. Our objective was to study the relationship between antibody response to 60 kilodalton chlamydial hsp and tubal factor infertility (TFI). SUBJECTS AND METHODS: Twenty-three women with TFI and 33 women with male factor infertility (controls) were studied. Tubal factor infertility was defined as infertility for one year with hydrosalpinx or distal tubal occlusion. Patients' sera were tested for antibodies to the chlamydial hsp using an enzyme-linked immunosorbent assay (ELISA). A stepwise logistic regression was performed by each patient's age, race/ethnicity, self-reported history of chlamydia infection, gonorrhea, or pelvic inflammatory disease (PID), history of ectopic pregnancy, and antibodies to the chlamydial hsp. RESULTS: Eighteen of the 23 women with TFI had a positive result on the hsp ELISA (78.6%) versus 23.4% of controls. Risk factors for TFI were a history of PID (P = 0.022), "nonwhite" race (P = 0.004), history of ectopic pregnancy (P = 0.027), and antibodies to the 60 kilodalton chlamydial hsp (P < 0.001). CONCLUSIONS: Antibodies to 60 kilodalton chlamydial hsp are strongly associated with TFI.